Effects of arsenic exposure on E2 and TRH and their receptor mRNA expressions in rats - Yuanyan LAI; Hongyun LI; Xiaowei MA; Zhihong JIANG; Jun WU (环境与职业医学, 2023)
BackgroundArsenic can enter the hypothalamus to induce estrogen effect and interfere with the function of the neuroendocrine system. The thyroid endocrine system (hypothalamic-pituitary-thyroid axis) is one of the main endocrine systems, and the mechanism of arsenic-induced thyroid endocrine toxicity is still unclear. ObjectiveTo investigate the effects of different arsenic exposure levels on estradiol (E2), hypothalamic thyrotropin-releasing hormone (TRH), and their receptor (ERα, ERβ, and TRHR) mRNAs in rats and the possible hypothalamic toxic pathway and mechanism. MethodsSeventy Wister rats were randomly divided a control group (sterile water); low-, medium-, and high-dose arsenic exposure groups [0.8, 4.0, and 20.0 mg·kg−1 sodium arsenite (NaAsO2)]; estrogen receptor inhibitor (ICI182780) intervention + low-, medium-, and high-dose arsenic exposure groups; with 10 animals in each group, half male and half female. Rats in the arsenic exposure groups were exposed to NaAsO2 by drinking water for 19 weeks, and rats in the intervention groups were injected with 0.5 mg·kg−1 ICI182780 via tail vein at week 9, 3 times a week. The levels of E2 and TRH in serum of rats were detected by ELISA. The expression levels of estrogen receptor α (ERα), estrogen receptor β (ERβ), and TRH receptor (TRHR) mRNAs in hypothalamus of rats were detected by real-time PCR (RT-PCR). Results(1) E2 and its receptor mRNA: Compared with the control group, the serum E2 level of female rats was increased in the low-dose and the medium-dose arsenic exposure groups (P<0.05), and the serum E2 level of male rats was increased in the low-dose, the medium-dose, and the high-dose arsenic exposure groups (P<0.05), and the change of female E2 was greater than that of male rats. Compared with the control group, the relative expression levels of ERα mRNA and ERβ mRNA in female rats were increased in the low-dose, the medium-dose, and the high-dose arsenic exposure groups (P<0.05), so were the relative expression levels of ERα mRNA in male rats (P<0.05). (2) TRH and its receptor mRNA: Compared with the control group, the serum TRH level of female rats was increased in the high-dose arsenic group (P<0.05), the relative expression level of TRHR mRNA was increased in the low-dose, the medium-dose, and the high-dose arsenic exposure groups (P<0.05). Results (1) and results (2) suggested that females were more likely than males to have abnormal changes in E2, TRH, and related receptor genes after arsenic exposure. (3) Compared with female rats in the medium-high dose arsenic exposure group, the expressions of TRH and TRHR induced by arsenic exposure were inhibited after the intervention of ICI182780 (P<0.05), suggesting that arsenic in the hypothalamus may have toxic effects on TRH and TRHR by inducing estrogen-like effects. ConclusionArsenic exposure can induce estrogen-like effects in the hypothalamus, interfere with thyroid function, and show dose-dependent and sex differences. E2 and TRH and their receptors may be the toxic pathway of arsenic-related estrogen-like effect.